2019
DOI: 10.1017/inp.2019.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indaziflam on native species in natural areas and rangeland

Abstract: Minimizing the negative ecological impacts of exotic plant invasions is one goal of land management. Using selective herbicides is one strategy to achieve this goal; however, the unintended consequences of this strategy are not always fully understood. The recently introduced herbicide indaziflam has a mode of action not previously used in non-crop weed management. Thus, there is limited information about the impacts of this active ingredient when applied alone or in combination with other non-crop herbicides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
25
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 41 publications
(85 reference statements)
9
25
2
Order By: Relevance
“…reported that indaziflam was an effective option for controlling invasive winter annual grasses such as downy brome ( Bromus tectorum L.), feral rye ( Secale cereale L.), and Japanese brome ( Bromus japonicus Thunb), allowing for increases in biomass and species richness 2 years after treatment. Other studies have reported similar findings with indaziflam in rangeland systems …”
Section: Introductionsupporting
confidence: 79%
“…reported that indaziflam was an effective option for controlling invasive winter annual grasses such as downy brome ( Bromus tectorum L.), feral rye ( Secale cereale L.), and Japanese brome ( Bromus japonicus Thunb), allowing for increases in biomass and species richness 2 years after treatment. Other studies have reported similar findings with indaziflam in rangeland systems …”
Section: Introductionsupporting
confidence: 79%
“…Indaziflam can remain in the soil for three or more years (Sebastian et al 2016b(Sebastian et al , 2017 while these sites were sampled 1 yr posttreatment. Previous work indicates that indaziflam does not negatively impact species richness or abundance 1 yr after treatment and may increase richness in the second year after treatment in rangelands of Colorado (Clark et al 2019;Sebastian et al 2016bSebastian et al , 2017. Species richness and diversity data from 2020, the second year after indaziflam application (data not presented), did not display an increase in species richness or diversity in this transitional ecoregion of northeast Wyoming.…”
Section: Treatmentmentioning
confidence: 64%
“…The control of invasive annual grasses results in an increase in growth of existing perennial plants due to reduced competition (Sebastian et al 2017a(Sebastian et al , 2020. Established perennial vegetation is largely unaffected by indaziflam (Clark et al 2019), likely because roots of perennial plants often extend below the zone of herbicide activity. However, new recruitment of a nonnative perennial species was inhibited by indaziflam (Sebastian et al 2017c), and it is likely that any germinating seeds in the zone of herbicide activity will not emerge, as indaziflam inhibits cellulose biosynthesis in the radicle and is nonselective (Brabham et al 2014).…”
Section: Introductionmentioning
confidence: 99%